PENGUKURAN MUTU WEB TERHADAP KEPUASAN BERTRANSAKSI BISNIS DENGAN ANALISA REGRESI SEDERHANA BAGI PENGGUNA MAHASISWA - Prasetyo, Arfhan (LPPM Universitas Nusa Mandiri, 2012)
Internet is information technology is earning easily in information seeking. The Internet made as without bound link, The information can be accessed every time without binding with infrastructure fulfilling in process of seeking the information. e-Commerce ( Electronic Commerce), this time medium in enthusing by the public. e-Commerce is a new breakthrough in the information world, e-Commerce can give information to the buyer in appearance and form which more drew and can be accessed any time every when time without bound. e-Commerce ( Electronic Commerce), this time medium in enthusing by the public. e-Commerce is a new breakthrough in the information world, e-Commerce can give information to the buyer in appearance and form which more drew and can be accessed any time every when time without bound. Sodium Maulina ( 2009) e-Commerce is conception has just which able to be described as goods sales process or service at Internet world wide web ( Shim, Qureshi, Siegel, 2000) or sales process or product transfer, service and information through information network is including internet ( Turban, Lee, king, Chung, 2000). This research aims to know how big influence quality of web to satisfaction transacts consumer business Students. Result of data analysis got result for variable Web quality ( X) with satisfaction transacts consumer business students ( Y) obtained correlation coefficient 0,710, thus inferential there is a relationship which is positive and significant between Web quality ( X) with satisfaction transacts consumer business students ( Y). Linear regression model formed Y = 16,168 + 0,680, X.